Implementation in Profile Matching Techniques Avsec (Aviation Security) Career Development - Alphonsus Liquori Sanfaris; A.A.N. Oka Suryadinatha Gorda (Enrichment : Journal of Management, 2020)
Career development process within the Aviation Security (Avsec) division I Gusti Ngurah Rai International Airport is one of the activities important in preparing the next generation who will determine the direction the development of this division going forward. Large number of personnel, with backgrounds diversity, is a challenge in itself for HR managers conduct an optimal and objective assessment in selecting the right personnel to be promoted. The assessment team should consider using the system right decision support. One of the methods that can be used as decision support system namely Profile matching. The way this method works is by calculating the competency gap, determining the core factor and secondary factor, calculates the total value until it ends at the determination stage ranking. Based on this, the authors will conduct research on implementation of profile matching techniques as a decision support system be objective in selecting personnel candidates to be promoted. This research involving 3 candidates and 5 aspects of the assessment that had been agreed upon previously, namely discipline, integrity, cooperation, service, and self-development. The output of the process the calculation of profile matching is the ranking of the candidate employees who will be get promoted. This will certainly help the assessment team as well as the internal leadership take decisions to determine the eligibility of the personnel to be promoted based on measurable assessments with the level of objectivity good.